Particle size and gastrointestinal absorption influence tiotropium pharmacokinetics: a pilot bioequivalence study of PUR0200 and Spiriva HandiHaler. Issue 3 (15th January 2019) - Perry, Jason; Trautman, Brian; Takher‐Smith, Joe; Kramer, Steve; Kane, Katie; Silverman, Michael; Tan, Lisa; Haughie, Scott; Richter, Wolfram; Kirkov, Valentin; Arsova, Sacha; Ward, Jonathan; et al.
Abstract : Aims: Plasma pharmacokinetics permit the assessment of efficacy and safety of inhaled drugs, and possibly their bioequivalence to other inhaled products. Correlating drug product attributes to lung deposited dose is important to achieving equivalence. PUR0200 is a spray‐dried formulation of tiotropium that enables more efficient lung delivery than Spiriva ® HandiHaler ® (HH). The ratio of tiotropium lung‐to‐oral deposition in PUR0200 was varied to investigate the impact of particle size on tiotropium pharmacokinetics, and the contribution of oral absorption to tiotropium exposure was assessed using charcoal block. Methods: A seven‐period, single‐dose, crossover study was performed in healthy subjects. PUR0200 formulations differing in dose and aerodynamic particle size were administered in five periods and Spiriva HH in two periods. In one period, Spiriva HH gastrointestinal absorption was blocked with oral charcoal. Tiotropium plasma concentrations were assessed over 8 h after inhalation. Results: PUR0200 pharmacokinetics were influenced by aerodynamic particle size and the ratio of lung‐to‐oral deposition, with impactor sized mass (ISM) correlating most strongly with exposure. Formulation PUR0217a (3 μg tiotropium) lung deposition was similar to Spiriva HH (18 μg) with and without charcoal block, but total PUR0200 exposure was lower without charcoal. The C max and AUC0–0.5h of Spiriva HH with and without charcoal block were bioequivalent; however, Spiriva HH AUC0–8h was lower when gastrointestinal absorption was inhibited with oral charcoal administration. Conclusions: Pharmacokinetic bioequivalence indicative of lung deposition and efficacy can be achieved by matching the reference product ISM. Due to reduced oral deposition and more efficient lung delivery, PUR0200 results in a lower AUC0– t than Spiriva HH due to reduced absorption of drug from the gastrointestinal tract.